2008
DOI: 10.1177/001440290807400401
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on Teaching Mathematics to Students with Significant Cognitive Disabilities

Abstract: This article reports on a comprehensive literature review and meta-analysis of 68 experiments on teaching mathematics to individuals with significant cognitive disabilities. Most of the studies in the review addressed numbers and computation or measurement. Within the computation studies identified, most focused on counting, calculation, or number matching. For the measurement studies, nearly all focused on money skills. Of the 54 single subject design studies, 19 were classified as having all quality indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
216
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(236 citation statements)
references
References 57 publications
4
216
1
9
Order By: Relevance
“…While research has shown that students with severe intellectual disabilities can learn some basic mathematics, the majority of studies focused on simple discriminations, such as number identification, money, or telling time (Browder, Spooner, Ahlgrim-Delzell, Wakeman, & Harris, 2008). In addition, there has been research to support general curriculum math instruction for some students with severe disabilities (Browder, Trela, Courtade, Jimenez, Knight, & Flowers, 2012;Jimenez, Browder, & Courtade, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While research has shown that students with severe intellectual disabilities can learn some basic mathematics, the majority of studies focused on simple discriminations, such as number identification, money, or telling time (Browder, Spooner, Ahlgrim-Delzell, Wakeman, & Harris, 2008). In addition, there has been research to support general curriculum math instruction for some students with severe disabilities (Browder, Trela, Courtade, Jimenez, Knight, & Flowers, 2012;Jimenez, Browder, & Courtade, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One reason may be that the curriculum is organised differently in the UK (Clough, 2006) [26] and the United States (Mulcahy et al, 2016) [27]. Another reason is that a number of studies about mathematics and special education have been performed with students with learning difficulties and emotional and behavioural disorders-most of the studies focused on the full range of developmental disabilities rather than focusing on students with significant intellectual disabilities (Browder et al, 2008) [28]. Moreover, the multiple strands and topics of mathematics is limited to number in the studies, therefore it is not clear what evidence exists for teaching the knowledge and skills for length in the measurement strand (Australian Curriculum Reporting and Assessment Authority, 2011a) [29].…”
Section: Purpose Of This Studymentioning
confidence: 99%
“…Based on their examination, technology-aided instruction, graphic organizers, the use of manipulatives, and explicit instruction had the evidentiary support required to establish EBPs for teaching mathematics to students with severe disabilities. Similar to the previous comprehensive review by Browder et al (2008), most of the articles analyzed skills which aligned with the NCTM's numbers and operations standard. …”
mentioning
confidence: 94%
“…Teaching students skills in mathematics represents the second most published literature for students with severe disabilities. In one of the first reviews on teaching mathematics to students with severe disabilities, Browder et al (2008) Browder et al (2008) found that most published studies taught skills within the National Council of Teachers of Mathematics (NCTM; 2000) numbers and operations and measurement standards, and the literature provided strong support for providing instruction on mathematical skills within in vivo settings.In an updated meta-analysis of research on teaching mathematical skills to students with severe disabilities, Spooner et al (2016) analyzed 36 total studies (33 SCD and three group experimental studies) published between January 2005 and August 2016. Of those 36 studies, 24 (22 SCD and two group studies) were evaluated to be of high or adequate quality, and were retained for analysis.…”
mentioning
confidence: 99%